Akses Kepada Keadilan bagi Anak - Saifuddin Saifuddin (Universitas Syiah Kuala, 2011)
ABSTRACT: Regardless of difference meaning and perception on justice, access to justice has been universally recognized in international system of human rights. Access to justice by the children in over the world is not an exemption part of the system. This essay aiming at discussing the availability of access to justice and offering effort to optimilize the access. The study reveals that, according to normative approach, the guarantee of access of the children to justice has been comprehensively administered on the convention of the rights of the child, national laws, and local laws in Aceh. At practical level, however, much should be done by both national and local government. It covers a rank of action from making a new law that support the best interest of the child to improve knowledge of the child on their own rights, as guaranted by the international, national, and local law. Access to Justice for Children